Analisis Dominasi Pajak Daerah Terhadap PAD Kabupaten Badung Tahun 2020-2024 - Ni Putu Divayanti Putri Cahyani; Nyoman Ari Surya Dharmawan; I Nyoman Putra Yasa (DAS Institute, 2026)
This study aims to analyze the dominance of local taxes in the Local Own-Source Revenue (PAD) of Badung Regency for the years 2020-2024. This study employs a descriptive quantitative method using the contribution ratio analysis technique. The data utilized consists of secondary data obtained from the Budget Implementation Report (LRA) of Badung Regency, published by the Regional Financial and Asset Management Agency (BPKAD) of Badung Regency. The results indicate that local taxes constitute the most dominant component of PAD compared to other PAD components, with an average contribution of 83,22%. The contribution of local taxes declined in 2020-2021 due to the COVID-19 pandemic, which impacted the decline in tourism and local economic activities. However, from 2022 to 2024, the contribution of local taxes increased again in line with the recovery of the tourism sector. The research results also indicate that the structure of Badung Regency’s PAD remains heavily reliant on local tax revenue from the tourism sector, thereby posing a potential fiscal risk in the event of a decline in tourism activity. Therefore, the local government needs to optimize the management of local taxes and develop the potential of other PAD components to ensure a more balanced and sustainable local revenue structure.